2016
DOI: 10.1063/1.4941563
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal crystallite suspensions studied by high pressure small angle x-ray scattering

Abstract: We report on high pressure small angle x-ray scattering on suspensions of colloidal crystallites in water. The crystallites made out of charge-stabilized poly-acrylate particles exhibit a complex pressure dependence which is based on the specific pressure properties of the suspending medium water. The dominant effect is a compression of the crystallites caused by the compression of the water. In addition, we find indications that also the electrostatic properties of the system, i.e. the particle charge and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…The application of pressure in the kbar range allows probing the volumetric response of soft matter and, in particular, to get insight into the degree of hydration . The response of the different conjugates to pressures up to 4000 bar was monitored with SAXS, which showed a decrease of ligand shell thickness with increasing pressure (Figure c; Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The application of pressure in the kbar range allows probing the volumetric response of soft matter and, in particular, to get insight into the degree of hydration . The response of the different conjugates to pressures up to 4000 bar was monitored with SAXS, which showed a decrease of ligand shell thickness with increasing pressure (Figure c; Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The possibility of gaining structural information in dense systems such as liquids or glasses was demonstrated in laser scattering experiments in the 1980s (Clark et al, 1983;Ackerson et al, 1985) and revived by X-ray studies of colloidal glasses (Wochner et al, 2009). In recent years, the potential of XCCA to study structures beyond gðrÞ has been investigated by various theories and simulation studies of two-dimensional systems (Altarelli et al, 2010;Kurta et al, 2012;Lehmkü hler et al, 2014;Malmerberg et al, 2015;Latychevskaia et al, 2015;Martin, 2017;, and shown experimentally for thin colloidal and polymer systems (Schroer et al, 2014(Schroer et al, , 2015Gutt et al, 2014;Liu et al, 2017), liquid crystals (Zaluzhnyy et al, 2016(Zaluzhnyy et al, , 2017 and colloids and nanocrystals (Mendez et al, 2014;Mancini et al, 2016;Schroer, Westermeier et al, 2016;Zaluzhnyy et al, 2017). In addition, cross-correlation has recently been demonstrated as a valuable tool for optimizing scattering signals of noisy data .…”
Section: Introductionmentioning
confidence: 99%
“…Applying pressure as a homogenous method to induce various structural transformations and phase transitions in pre-ordered nanoparticle assemblies has only recently been done. [23][24][25][26][27] Wu et al…”
mentioning
confidence: 99%